Computational investigation of proton transfer, pKa shifts and pH‐optimum of protein–DNA and protein–RNA complexes. Issue 2 (5th January 2017) - Peng, Yunhui; Alexov, Emil
ABSTRACT: Protein–nucleic acid interactions play a crucial role in many biological processes. This work investigates the changes of pKa values and protonation states of ionizable groups (including nucleic acid bases) that may occur at protein–nucleic acid binding. Taking advantage of the recently developed pKa calculation tool DelphiPka, we utilize the large protein–nucleic acid interaction database (NPIDB database) to model pKa shifts caused by binding. It has been found that the protein's interfacial basic residues experience favorable electrostatic interactions while the protein acidic residues undergo proton uptake to reduce the energy cost upon the binding. This is in contrast with observations made for protein–protein complexes. In terms of DNA/RNA, both base groups and phosphate groups of nucleotides are found to participate in binding. Some DNA/RNA bases undergo pKa shifts at complex formation, with the binding process tending to suppress charged states of nucleic acid bases. In addition, a weak correlation is found between the pH‐optimum of protein–DNA/RNA binding free energy and the pH‐optimum of protein folding free energy. Overall, the pH‐dependence of protein–nucleic acid binding is not predicted to be as significant as that of protein–protein association. Proteins 2017; 85:282–295. © 2016 Wiley Periodicals, Inc.